2008
DOI: 10.1051/0004-6361:20078622
|View full text |Cite
|
Sign up to set email alerts
|

Metallicity and effective temperature of the secondary of RS Ophiuchi

Abstract: Context. The recurrent nova RS Ophiuchi undergoes nova eruptions every ∼10−20 years as a result of thermonuclear runaway on the surface of a white dwarf close to the Chandrasekhar limit. Both the progress of the eruption and its aftermath depend on the (poorly known) composition of the red giant in the RS Oph system. Aims. Our aim is to understand better the effect of the giant secondary on the recurrent nova eruption. Methods. Synthetic spectra were computed for a grid of M-giant model atmospheres having a ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 30 publications
(24 reference statements)
1
42
0
Order By: Relevance
“…The count rate on day 26.1 is significantly lower than that on day 13.8, and the shape of the continuum is different. On day 26.1, a new component is observed longward of ∼ 20 Å (Nelson et al 2008) that could be associated with the SSS spectrum that was clearly detected three days later with Swift (Osborne et al 2008). However, the spectral shape of this new component on day 26.1 is quite different from the spectra observed on days 39.7, 54.0, and 66.9 (next three panels).…”
Section: Description Of Spectramentioning
confidence: 79%
See 3 more Smart Citations
“…The count rate on day 26.1 is significantly lower than that on day 13.8, and the shape of the continuum is different. On day 26.1, a new component is observed longward of ∼ 20 Å (Nelson et al 2008) that could be associated with the SSS spectrum that was clearly detected three days later with Swift (Osborne et al 2008). However, the spectral shape of this new component on day 26.1 is quite different from the spectra observed on days 39.7, 54.0, and 66.9 (next three panels).…”
Section: Description Of Spectramentioning
confidence: 79%
“…The SSS phase was observed after day ∼ 30 and ended before day ∼ 100 after outburst (Osborne et al 2008). Three highresolution X-ray spectra were taken during this phase which are described by Ness et al (2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Livio & Truran 1994;Schwarz et al 2001Schwarz et al , 2007. Although N is also enhanced in the atmosphere of the red giant component of RS Oph ([N/H]=0.6±0.3), its moderate C/N=0.16 (Pavlenko et al 2008) indicates this N enhancement is not as strong as that in the nova ejecta. Systematic studies of photospheric abundances of a few dozens symbiotic giants revealed N/O 0.5 and C/N 0.2, and they are consistent with moderate enhancement of N and depletion of C as expected for their evolutionary stage (Ga lan et al 2016(Ga lan et al , 2017.…”
Section: Uv and Optical Spectroscopymentioning
confidence: 96%